EVALUASI FITUR SCANNING DAN KINERJA TRANSMISI DATA MODUL HC-05 VERSI 2.0 DENGAN VERSI 3.0 DI LINGKUNGAN LINE OF SIGHT (LOS) - Muhammad Sabirin Hadis; Muhammad Rizal; Annisa Nurul Puteri; Akbar Hendra (Jurusan Teknik Informatika dan Komputer, 2020)
This study examines the scanning features and compares the data transmission performance of the HC-05 version 2.0 module with the HC-05 version 3.0 module using distance and data size parameters. Scanning feature testing aims to ensure this feature can function adequately on each HC-05 module. Data transmission performance was tested using data packet size parameters with variations of 10 bytes, 100 bytes, and 500 bytes and sending distances with changes of 10 meters, 20 meters, 40 meters, 60 meters and 80 meters. The results of the data transmission performance are compared to find out which version has the most optimal performance. Based on the tests carried out, HC- 05 version 2.0 is the best module to be used in Line of Sight (LoS) environmental conditions because the scanning feature functions according to the instructions of the datasheet and the data transmission performance runs smoothly, the maximum distance reaches 89 meters. While the HC-05 version 3.0 scanning feature does not function properly, and data transmission performance only reaches a distance of 60 meters.